Analisis Pola Downtime untuk Optimalisasi Strategi Perawatan Sistem Navigasi Kapal (Studi Kasus: PT. Pawitra Daya Teknik) - Ahmad Ainur Rozikin; Herlina Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the downtime patterns of ship navigation systems to formulate an optimal preventive maintenance strategy to improve operational efficiency. A case study was conducted at PT Pawitra Daya Teknik using historical data of 113 work orders from 11 ships during December 2025–February 2026. Methods include descriptive analysis, MTTR, MTBF, availability calculations, statistical distribution testing (Minitab), exponential reliability function, age replacement model, and cost comparison between reactive and preventive scenarios. Results show that Radar and GPS are the most critical systems (contribute >59% of downtime duration) with software failures as the main cause (42%). The optimal preventive maintenance intervals are differentiated: Radar and GPS are serviced more frequently (every 260 hours and 410 hours, respectively), while other systems are serviced less often. This strategy reduces annual downtime by 21.6%, increases availability by 0.26%, and generates operational cost savings of approximately IDR 409 million per year. In conclusion, the preventive maintenance strategy based on a 60% reliability target is proven to be technically and economically optimal.